Pembuatan pupuk kompos dari feses ternak kambing Peranakan Ettawa (PE): Production compost fertilizer from waste of Ettawa Breed (PE) - Sihombing, Dewi E.; Kertiyasa, I K. Y.; Kadju, Fransiskus Y. D.; Gusri, Rahmat; Suharto, Prihutomo (Fakultas Peternakan Universitas Papua, 2025)
ABSTRACT Processed livestock waste, especially goat manure, has the potential to be managed into organic fertilizer such as compost which can be used to increase environmental support, increase crop production, increase farmer income and reduce the impact of environmental pollution. Implementation of community service is carried out through providing knowledge and direct practice in processing Ettawa Peranakan goat waste. This implementation is directed at increasing competitiveness through increasing the capacity and competence of human resources (HR). Training on making organic fertilizer from goat waste as a replacement or reduction in the use of chemical fertilizers. This activity was carried out at the Technical Implementation Unit (UPT) for Animal Breeding and Animal Feed Production in Sumlili Village, West Kupang District, Kupang Regency. The activity lasted for 1 month and included Compost Fertilizer from PE Goat Feces. This activity was carried out using the Participatory Rural Approach (PRA) approach, which is a method of educating the community through counseling, training, demonstrations/demonstrations (demonstration plots). This activity includes education and composting practices. The results of PKM activities show an increase and understanding of breeders. This increase in understanding of the knowledge and methods of making compost has a positive impact on the management of raising Etwa Peranakan goats and the use of livestock waste into organic fertilizer which has a higher nutritional value, which will result in a higher selling value and is expected to increase income at the UPT. Keywords: Compost; Feces: Goat; Organic; Waste ABSTRAK Pengolahaan limbah peternakan khususnya kotoran ternak kambing memiliki potensi untuk dikelola menjadi pupuk organik seperti kompos yang dapat dimanfaatkan untuk meningkatkan dukung lingkungan, meningkatkan produksi tanaman, meninkatakan pendapatan peternak dan mengurangi dampak pemcemaran lingkungan. Pelaksananan pengabdian Kepada Masyarakat dilakukan melalui pemberian ilmu pengetahuan dan praktik langsung dalam pengelohan limbah kotoran ternak kambing Peranakan Etawa. Pelaksanan ini diarahkan untuk peningkatakn daya saing melalui peningkatan kapasitas dan kelambagaan Sumber daya manusia (SDM). Pelatihan Pembuatan pupuk organik dari limbah kotoran ternak kambing sebagai pengganti ataupun pengurangan penggunaan pupuk kimia. Kegiatan ini dilaksanakan di Unit Pelaksanaan Teknis (UPT) Pembibitan Ternak dan Produksi Pakan Ternak di Desa Sumlili, Kecamatan Kupang Barat, Kabupaten Kupang. Kegiatan berlangsung selama 1 bulan mencakup Pupuk Kompos dari Feses Ternak Kambing PE. Kegiatan ini dilakukan menggunakan metode pendekatan Participatory Rural Approach (PRA) yaitu suatu metode pendidikan kepada masyarakat melalui penyuluhan, pelatihan, demontrasi/ percontohan (demplot). Kegaitan ini mencakup penyuluhan dan praktik pembuatan kompos. Hasil kegiatan PKm menunjukan adanya peningkatan dan pemahaman peternak. Peningakatan pada pemahaman terhadap pengatahuan dan cara pembuatan kompos ini berdapak positif terhadap manajemen pemeliharan ternak kambing Peranakan Etwa dan pemanfaatan limbah peternakan menjadi pupuk organik yang memiliki nilai nutrisi lebih tinggi sehingga akan membuat nilai jual lebih tinggi sehingga diharapkan mampu meningkatkan pendapatan di UPT. Kata kunci: Feses; Kambing; Kompos: Limbah; Organik